Cancer Stem Cells in Moderately Differentiated Lip Squamous Cell Carcinoma Express Components of the Renin–Angiotensin System - Ram, Rachna S. (Front Surg, 2017)
AIM: We investigated the expression of the renin–angiotensin system (RAS) by cancer stem cell (CSC) subpopulations we have identified in moderately differentiated lip squamous cell carcinoma (MDLSCC). METHOD: Ten MDLSCC samples underwent 3,3-diaminobenzidine (DAB) and immunofluorescent immunohistochemical (IHC) staining for (pro)renin receptor (PRR), angiotensin-converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1), and receptor 2 (ATIIR2). NanoString analysis and Western blotting (WB) were performed on six MDLSCC samples for gene and protein expression, respectively. RESULTS: IHC staining showed expression of PRR, ATIIR1, and ATIIR2 on cells within the tumor nests (TNs) and the stroma. ACE was localized to the microvessels within the stroma. WB detected PRR, ACE, and ATIIR2. NanoString analysis confirmed gene expression of PRR, ACE, and ATIIR1. CONCLUSION: Components of the RAS: PRR, ATIIR1, and ATIIR2 are expressed on two CSC subpopulations in MDLSCC, one within the TNs and the other within the stroma. The endothelium of the microvessels within the stroma expresses ACE.